Mineralogy and Concentration of Potentially Toxic Elements in Soils of the São Francisco Sedimentary Basin - Edilene Pereira Ferreira; Ricardo Marques Coelho; Gustavo Souza Valladares; Laura Milani da Silva Dias; Ana Carolina Cunha de Assis; Rafael Cipriano da Silva; Antonio Carlos de Azevedo; Cleide Aparecida de Abreu (Revista Brasileira de Ciência do Solo, 2018)
ABSTRACT Lithological and geomorphological variations determine formation of soils with different mineralogical constitutions and can influence the distribution of potentially toxic elements (PTE). The aim of this study was to determine the contents of PTE and mineralogical assemblages along soil profiles of different classes and parent materials and to investigate the association among these factors in the São Francisco sedimentary basin in the northern part of the state of Minas Gerais (Brazil). Eight soil pedons of different classes that developed from different parent materials (limestone, siltstone, phyllite, alluvial-colluvial sediments, detrital cover, and rhythmite) were studied in two lithotoposequences. Soil morphological, particle-size, and chemical analyses were carried out for soil characterization and classification. A mineralogical investigation was carried out by X-ray diffraction on soil sand, silt, and clay fractions. Potentially toxic elements were extracted by microwave-assisted acid digestion (EPA 3015A method) and determined in an ICP-OES. Soil mineralogy showed relevant interactions between pedogenesis and morphogenesis. Quartz is the main mineral in the sand and silt fractions, with varying amounts of weatherable primary minerals, whereas kaolinite is the main mineral in the clay fraction, followed by 2:1 clay minerals and oxides. The main soil properties associated with PTE variability were pH, redox environment, mineral and organic reactive surfaces, and clay content. The unique patterns of PTE distribution per pedon and differences in PTE contents in soils from the same parent material, but with different pedogenic evolution, showed that pedogenic processes influence PTE distribution. Mainly Mn, Ni, Pb, and Ba were influenced by parent material, especially limestone, siltstone, and detrital cover, but Cd, As, and Cu were also influenced. To a lesser extent, Mo was influenced by phyllite and Cr by detrital cover and phyllite. Rhodic Ferralsol (Latossolo Vermelho Distrófico típico) was the only taxonomic class to show class association with PTE. The association of Ferralsols (Latossolos) with Cd, Mn, Ni, Pb, Ba, As, and Cu and the low contents of these elements in soils of this class suggest that pedogenic processes common to Ferralsol (Latossolo) evolution are responsible for decreasing levels of these PTE.